2009
DOI: 10.1021/ol900541n
|View full text |Cite
|
Sign up to set email alerts
|

CuBr-Catalyzed Oxidative Difluoromethylation of Tertiary Amines with Difluoroenol Silyl Ethers

Abstract: CuBr-catalyzed oxidative difluoromethylation of readily available tertiary amines with difluoroenol silyl ethers was performed under mild conditions to afford beta-amine-alpha,alpha-difluoro ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(29 citation statements)
references
References 56 publications
0
27
0
2
Order By: Relevance
“…For example, a,a-difluoro carbonyl compounds are known to form relatively stable hydrates, the feature that renders them inhibitors of wide range of the enzymatic cleavage of peptide bonds [8]. Consequently, synthesis of this type of compounds, in particular, b-amino-a,a-difluoro ketone or acid derivatives has received appropriate attention [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a,a-difluoro carbonyl compounds are known to form relatively stable hydrates, the feature that renders them inhibitors of wide range of the enzymatic cleavage of peptide bonds [8]. Consequently, synthesis of this type of compounds, in particular, b-amino-a,a-difluoro ketone or acid derivatives has received appropriate attention [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite progresses in this area [9], one interesting structural type of fluorinated sulfonamides of type 2 (Fig. 1), bearing pharmacophoric b-amino carbonyl moiety, is still hitherto unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[23] The authors propose that the reaction mechanism is similar to that previously reported for the coupling of dialkylmalonates to isoquinolines, that is, the formation of a copper-imminium ion to which the nucleophilic difluoroenol silyl ether adds. Initially the reaction between isoquinolines and difluoroenol silyl ethers was investigated under the same conditions reported by Li and coworkers.…”
Section: Cdcs Catalyzed By Copper(i) and (Ii) Complexesmentioning
confidence: 52%
“…We have tried to improve the catalytic result through introducing more hydrogen bond donors into chiral guanidine catalysts (3k, 3l). Unfortunately, the expected improvement of reaction result was not found (Table 1, entries [11][12]. The substitution of the trimethylsilyl group with a dimethylphenylsilyl group on the acylsilane gives a higher yield (81%) with slightly lower dr (16 : 1) and similar ee value (91%) ( Table 1, entry 13).…”
Section: Resultsmentioning
confidence: 99%
“…Since their discovery by Brook in 1957, 1-3 acylsilanes have been the one of the most powerful and efficient compounds that have the silicon directly attached to the carbonyl group, exhibiting particular physical and chemical properties, [4][5][6][7][8] so that they can be easily transformed into many different derivatives in one pot, such as acid, 9-12 ketone, [13][14][15] alcohol, 16,17 aldehyde, 11,18,19 cyanogen, 20 amide 12,20,21 and ester. 20,22 In addition to these radical reactions, a great deal of effort has been devoted to the development of various other kinds of acylsilane reactions, for instance, stereocontrolled nucleophilic additions, 23 stereocontrolled aldol reactions, 24 cyclization, 25 coupling reaction, 26 α-halogenations, 3 and enantioselective reduction.…”
Section: Introductionmentioning
confidence: 99%